Pendidikan Pesantren Sebagai Modal Kecakapan Hidup - M Yusuf (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
Education can be interpreted as a human activity to maintain the continuation of life (survival) as individuals and as members of society, in the form of inheritance of knowledge, values, culture and skills from one generation to another in order to maintain the identity of civilization. There needs to be support from various groups for a student so that he is able to carry out its function as a true learner human being such as the environment, society, government. and also very crucial is the family or parents. The pesantren is also one of the wombs which incites warriors who, besides being militants, are also fully responsible for their duties and environment. Responsible vertically or horizontally in giving birth and raising Indonesia. And the current battleground is the existence of various problems faced by people both internally and internally. From this point on, pesantren must appear as capital and life modules as a solutive step towards the various problems faced by their learners as life skills. Life skills need to be mastered by every citizen in facing the challenges of life change that contains a variety of intense competition in meeting the needs of life. With its uniqueness, pesantren has millions of ways to forge students (read; santri) from various abilities as mandated by the law through learning character education, critical thinking, socializing, and also internalizing skills through the habituation method